(untitled) (ModaPalavra e-periódico, 2021)
With the use of the concepts of greimasian semiotics, this article analyzes the institutional video present on Pantys brand site, which offers absorbing pantys, shorts, swimsuits and bras to a female public that searches inovative and sustainable alternatives, in order to identify the brand’s discourse through one of its manifestations. Were used the levels of the generative path of sense to perform the analysis, as well as the categories of the expression plan and the semi-symbolism.